Pregnant Women With Dermatomyositis or Polymyositis - Fasoulakis N. Zacharias; Galanopoulos G. Nikolaos; Kontomanolis N. Emmanuel (Gynecology and Obstetrics Research, 2024)
Dermatomyositis (DM) and polymyositis (PM) belong to the group of inflammatory muscle diseases characterized by inflammation of the muscles. These diseases are usually studied together as dermatomyositis/polymyositis (DM/PM). Regarding pregnant patients affected with DM/PM, important individual issues arise as: (1) Do female patients with DM/PM successfully complete pregnancy, giving birth to healthy infants or is there high risk of complications for both mother and fetus? (2) Is there a connection between activity of DM/PM and high risk of complications during gestation? (3) Does pregnancy increase the risk of DM/PM activation? (4) Does pregnancy increase the risk of DM/PM relapse during or right after gestation? After our attempt to answer these questions, we will refer to the treatment of the disease during pregnancy and the effect it could have on the completion of pregnancy.